A study of multi-jet events at the CERN p̄p collider and a search for double parton scattering - Alitti, J; Ambrosini, G; Ansari, R; Autiero, D; Bareyre, P; Bertram, I; Blaylock, G; Bonamy, P; Borer, K; Bourliaud, M; Buskulic, D; Carboni, G; et al. (1991)
A study of events containing at least four high transverse momentum jets and a search for double parton scattering (DPS) have been performed using data collected with the UA2 detector at the CERN p̄p Collider (√s=630 GeV). The results are in good agreement with leading order QCD calculations. A value of σDPS<0.82 nb at 95% confidence level (CL) is obtained for the DPS cross section.